The senses perceive the meanings of graphic processors on smartphones - Hanan Ahmed; Hanan Samir Abd Elazem (Journal of Architecture, Art & Humanistic Science, 2024)
Perception is a processing of information that comes from the senses to the brain, so that the complex central nervous system determines, organizes and interprets information to understand the world around us, and one of the most important senses is the sense of sight, which includes external visual vision, mental vision, imaginative and internal emotional, through which the human mind adds The meaning depends on the sensory perceptions that it receives, whatever they are. When you see a shape, the eye keeps searching for the meaning of its parts. Visual perception is the ability to interpret the surrounding environment, by interpreting information within visible light. Aesthetic perception is a process of mental activity that takes place after receiving signals emitted from graphics. Through the senses, which is the ability to feel the artwork, whether plastic works or videos loaded on mobile phones, which have become apparent to a large segment of society in displaying and watching artworks through mobile phones, which are affected by various factors on which the perception of the senses of the recipient who enjoys a prior visual culture depends. For artistic work as a result of the stability of the formal perceptions of the work of art.The research problemWhat are the factors that affect the perception of the meanings of the mobile graphic processors on smart phones?Is the process of sensory perception of the meanings of motion graphics affected on smartphones?The research aims:Determine the perception factors that are affected by mobile graphics processors on smartphones.Emphasis on the aspects of the process of perception of the senses of the meanings of the animated graphics on smartphonesresearch importance:Standing on the modern capabilities of smartphones in running animated graphics.Emphasizing of the complementarity of the senses in perceiving the animation graphics in smartphones.